2010
DOI: 10.1007/s10792-010-9366-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein angiographic findings and clinical features in Fuchs’ uveitis

Abstract: Fuchs' uveitis is very often diagnosed with substantial delay, which is at the origin of deleterious effects such as unnecessary treatment and its consequences. The aim of this study was to analyse the type and frequency of posterior inflammatory and fluorescein angiographic signs in Fuchs' uveitis in conjunction with other clinical signs. Patients seen at the Centre for Ophthalmic Specialised Care (COS) in Lausanne and the Memorial A. de Rothschild, Clinique Générale-Beaulieu in Geneva between 1995 and 2008 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 21 publications
3
35
0
Order By: Relevance
“…It is important to consider FUS in uveitic eyes with prominent vitreous inflammation/debris with FA showing disc hyperfluorescence and absence of CME. 24 Bouchenaki et al 32 suggested that the high frequency of disc hyperfluorescence fundus fluorescein angiography could be due to an inflammatory breakdown of the blood-ocular barrier, or secondary to mechanical traction by a heavily infiltrated vitreous proximal to the optic disc. However this could not be found in the present series.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider FUS in uveitic eyes with prominent vitreous inflammation/debris with FA showing disc hyperfluorescence and absence of CME. 24 Bouchenaki et al 32 suggested that the high frequency of disc hyperfluorescence fundus fluorescein angiography could be due to an inflammatory breakdown of the blood-ocular barrier, or secondary to mechanical traction by a heavily infiltrated vitreous proximal to the optic disc. However this could not be found in the present series.…”
Section: Discussionmentioning
confidence: 99%
“…The features described in these eyes include the presence of chronic persistent iritis, diffuse, fine, stellate keratic precipitates, diffuse iris atrophy and/or heterochromia, absence of posterior synechiae, posterior subcapsular cataract formation, vitritis, sectoral peripheral retinal vascular leakage, disc hyperfluorescence on fluorescein angiography and the development of cystoid macula oedema after cataract surgery [45 ]. The patients may be asymptomatic or present with floaters or visual loss from cataract formation or glaucoma.…”
Section: Rubella Virusmentioning
confidence: 99%
“…A relatively mild disruption of the blood-aqueous barrier has been shown in eyes with Fuchs' uveitis (FU), with mean flare values ranging from 6.4 to 12.1 ph/ms that were still significantly higher compared with fellow eyes or eyes of healthy controls [32][33][34][35][36][37]. It is noteworthy that flare levels do not change with anti-inflammatory Review CME treatment and remain stable over months or years in this entity [7,37,38].…”
Section: Fuchs' Uveitismentioning
confidence: 99%
“…It is noteworthy that flare levels do not change with anti-inflammatory Review CME treatment and remain stable over months or years in this entity [7,37,38]. A relatively mild and stable breakdown of the blood-aqueous barrier has been reported in FU even after cataract surgery [33,36,39,40].…”
Section: Fuchs' Uveitismentioning
confidence: 99%